Analysis of Wasathiyyah Islamic Values in Semarang As-Sa'adah Islamic Boarding School Curriculum Perspective of M. Quraish Shihab - Rofi'ah, Haning; Thomafy, Khoiriyah (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This research aims to describe the meaning of wasathiyyah according to M. Quraish Shihab's perspective, the extent to which wasathiyyah Islamic values are compatible in As-Sa'adah Islamic boarding school curriculum and the personality of the students after the instillation of Wasathiyyah Islam at the As-Sa'adah Islamic Boarding School. This research uses descriptive qualitative method; then the data analysis technique uses inductive qualitative data analysis, which is carried out through observation, documentation, and the development of relationship patterns from previous data. This research shows that the wasathiyyah perspective of Quraish Shihab shows principles that advocate balance, tolerance, and a middle attitude in carrying out religious teachings. The wasathiyyah approach to religion encourages people to avoid extremism and fanaticism. As-Sa'adah Islamic Boarding School teaches wasathiyyah values through the study of kitab kuning material and also habituation activities at the Islamic boarding school, thereby producing superior students with good personalities, namely politeness, independence, and strong beliefs. The limitation of this research is that it only uses the As-Sa'adah Islamic Boarding School curriculum as the only research object, in this case it is not representative. Recommendations for further research are to add research objects related to the Islamic boarding school curriculum.